PENGARUH GAYA KEPEMIMPINAN, PEMBERDAYAAN KARYAWAN DAN DUKUNGAN ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN KAYUMANIS JIMBARAN PRIVATE ESTATE & SPA, BALI - Dhyana, I Gusti Agung Kristana; Adnyani, I Gusti Ayu Dewi (E-Jurnal Manajemen, 2018)
Employee satisfaction level has an important role in achieving company goals. There are several factors that can support the achievement of employee job satisfaction such as employee empowerment, leadership style and also organizational support. The purpose of this study is to determine the influence of leadership style, employee empowerment, and also organizational support to employee job satisfaction Kayumanis Jimbaran Private Estate & Spa Bali. The population of this research is all employees at Kayumanis Jimbaran Private Estate & Spa Bali, amounting to 133 people, with the technique of determining the sample used is saturated or census sampling, then all members of the population made respondents in the study. Data were analyzed using multiple linear regression analysis technique. The results showed that leadership style, empowerment of employees, and partial organizational support have a positive and significant impact on employee job satisfaction Kayumanis Jimbaran Private Estate & Spa Bali. This has the meaning that the better the application of leadership style, employee empowerment, and organizational support, the more increasing the level of job satisfaction of Kayumanis Jimbaran Private Estate & Spa Bali employees. Keywords : leadership style, employee empowerment, organizational support, job satisfaction